Digitally engendering soft skills through stixy – a web-based Bulletin Board - Ng, Shi Ing; Tan, Choon Keong; Yeo, Li Min; Lee, Kean Wah (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2012)
There have been complaints by private sectors about the quality of local graduates as an employable asset which for private sectors are paramount for career and industry success. In an effort to imbue local undergraduates with requisite soft skills, Higher Education Institutions (HEIs) are tasked to comply with the Malaysian Qualifications Framework to guarantee quality of soft skills among graduates. Traditionally, soft skills are learnt while pre-service teachers are engaged in project related assignments while assessment of soft skills is done during Q&A sessions. However, there is a possibility of developing soft skills by using Web 2.0 tools during learning. This study investigates the efficacy and the extent of the suitability of a free formed, web-based bulletin board, Stixy, as a learning platform to inculcate soft skills through collaborative knowledge building. Thirty eight first year TESL pre-service teachers at Universiti Malaysia Sabah (UMS) used Stixy as a bulletin board to contribute and discuss ideas in the process of creating a poster for an English Language literature assignment. Using elicitation tools such as questionnaire, focus-group interviews, reflective journals, both quantitative and qualitative data were gathered. Quantitative data were analysed descriptively using mean and standard deviation, while qualitative data were content analysed using the Collaborative Learning Conversation Skills Taxonomy (CLCS). Findings indicate that Stixy has succeeded in promoting soft skills through collaborative knowledge building and was adopted favorably by the pre-service teachers.